Neuropsychological differential diagnosis of Alzheimer’s disease and vascular dementia: a systematic review with meta-regressions - Sokolovič, Leo; Hofmann, Markus J.; Mohammad, Nadia; Kukolja, Juraj (Frontiers in Aging Neuroscience, 2023)
Introduction Diagnostic classification systems and guidelines posit distinguishing patterns of impairment in Alzheimer’s (AD) and vascular dementia (VaD). In our study, we aim to identify which diagnostic instruments distinguish them. Methods We searched PubMed and PsychInfo for empirical studies published until December 2020, which investigated differences in cognitive, behavioral, psychiatric, and functional measures in patients older than 64 years and reported information on VaD subtype, age, education, dementia severity, and proportion of women. We systematically reviewed these studies and conducted Bayesian hierarchical meta-regressions to quantify the evidence for differences using the Bayes factor (BF). The risk of bias was assessed using the Newcastle-Ottawa-Scale and funnel plots. Results We identified 122 studies with 17,850 AD and 5,247 VaD patients. Methodological limitations of the included studies are low comparability of patient groups and an untransparent patient selection process. In the digit span backward task, AD patients were nine times more probable (BF = 9.38) to outperform VaD patients (βg = 0.33, 95% ETI = 0.12, 0.52). In the phonemic fluency task, AD patients outperformed subcortical VaD (sVaD) patients (βg = 0.51, 95% ETI = 0.22, 0.77, BF = 42.36). VaD patients, in contrast, outperformed AD patients in verbal (βg = −0.61, 95% ETI = −0.97, −0.26, BF = 22.71) and visual (βg = −0.85, 95% ETI = −1.29, −0.32, BF = 13.67) delayed recall. We found the greatest difference in verbal memory, showing that sVaD patients outperform AD patients (βg = −0.64, 95% ETI = −0.88, −0.36, BF = 72.97). Finally, AD patients performed worse than sVaD patients in recognition memory tasks (βg = −0.76, 95% ETI = −1.26, −0.26, BF = 11.50). Conclusion Our findings show inferior performance of AD in episodic memory and superior performance in working memory. We found little support for other differences proposed by diagnostic systems and diagnostic guidelines. The utility of cognitive, behavioral, psychiatric, and functional measures in differential diagnosis is limited and should be complemented by other information. Finally, we identify research areas and avenues, which could significantly improve the diagnostic value of cognitive measures.